Study of Marital Satisfaction in Autistic Families - A.M. Ghahjavarestani; M. Badia; J.S. Gavaldà (Moscow State University of Psychology and Education, 2020)
The aim of this study was to investigate the quality of marital relations and family performance in parents of children with autism in 110 different questions. In this test, the coefficient was examined on 10 scales in 8 items. 51 families with at least one child with autism in Iran was tested. To assess the quality of marital relationships, marital adjustment, and family functioning, all parents completed the AMSS (Afrooz Marital Satisfaction Scale) questionnaire. The study, which looked at families' satisfaction with autism, found that there was a significant relationship between the quality of marital relationships and mental health in families with children with autism, based on all our hypotheses. This study and other similar studies show that families need ongoing programs. These programs include identifying, finding solutions, and providing direct advice to families. In this program, we will see a reduction in stress and conflict among families with autism, a correct and thoughtful approach to family members, and people with autism. This program should be done in groups and separately in autism centers and other psychological and counseling offices.